2014
DOI: 10.1049/iet-com.2014.0141
|View full text |Cite
|
Sign up to set email alerts
|

Channel estimation with iterative discrete Fourier transform‐based smoothing for orthogonal frequency‐division multiplexing systems with non‐uniformly spaced pilots in channels with long delay spread

Abstract: An orthogonal frequency-division multiplexing (OFDM) system with non-uniformly spaced pilots, such as worldwide interoperability for microwave access, voids virtually all discrete Fourier transform (DFT)-based interpolation methods for channel estimation, because they all require pilots to be uniformly spaced. Therefore, we propose two iterative algorithms to solve this problem. In the proposed algorithms, the inverse discrete Fourier transform and DFT are iteratively used to smooth the channel frequency respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For type-A symbols, the estimation strategy is similar to the one proposed in [9], in which IFFT and FFT are iteratively employed as a type of smoothing filter. To further improve the estimation accuracy, decision feedback is also implemented.…”
Section: Proposed Channel Estimation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For type-A symbols, the estimation strategy is similar to the one proposed in [9], in which IFFT and FFT are iteratively employed as a type of smoothing filter. To further improve the estimation accuracy, decision feedback is also implemented.…”
Section: Proposed Channel Estimation Methodsmentioning
confidence: 99%
“…It is shown that the performance of this approach with only a small number of iterations is comparable to that of the decision-directed approach in some cases [9], but without the burden of constructing an encoder inside the receiver. Considering these factors, we use the…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations